2013
DOI: 10.5194/acp-13-147-2013
|View full text |Cite
|
Sign up to set email alerts
|

On the relationship between total ozone and atmospheric dynamics and chemistry at mid-latitudes – Part 1: Statistical models and spatial fingerprints of atmospheric dynamics and chemistry

Abstract: Abstract. We use statistical models for mean and extreme values of total column ozone to analyze "fingerprints" of atmospheric dynamics and chemistry on long-term ozone changes at northern and southern mid-latitudes on grid cell basis. At each grid cell, the r-largest order statistics method is used for the analysis of extreme events in low and high total ozone (termed ELOs and EHOs, respectively), and an autoregressive moving average (ARMA) model is used for the corresponding mean value analysis. In order to … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
59
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(66 citation statements)
references
References 64 publications
(14 reference statements)
6
59
0
1
Order By: Relevance
“…1a) indicate evident TCO negative trends over the North Pacific, East Asia, Caspian Sea and the northwestern Atlantic Ocean; whereas the TCO decreasing trends over the northeastern Pacific, northwestern North America, the southwestern Atlantic Ocean, Europe and Central Siberia (45°-60°N, 85°-120°E) are weak and even reversed over some regions. Similar features in TCO trends in the northern middle latitudes can be also found in Frossard et al (2013) which separated the TCO trend attributed to ODSs from that due to dynamical variabilities. The above features are more noticeable in the linear trend map of TCO anomalies with zonal mean removed (Fig.…”
Section: Methodssupporting
confidence: 58%
“…1a) indicate evident TCO negative trends over the North Pacific, East Asia, Caspian Sea and the northwestern Atlantic Ocean; whereas the TCO decreasing trends over the northeastern Pacific, northwestern North America, the southwestern Atlantic Ocean, Europe and Central Siberia (45°-60°N, 85°-120°E) are weak and even reversed over some regions. Similar features in TCO trends in the northern middle latitudes can be also found in Frossard et al (2013) which separated the TCO trend attributed to ODSs from that due to dynamical variabilities. The above features are more noticeable in the linear trend map of TCO anomalies with zonal mean removed (Fig.…”
Section: Methodssupporting
confidence: 58%
“…However, for Arosa's PC score 3 the QBO1 covariate has EDF of 0.2 (Table 1), thus it is insignificant. In addition, Frossard et al (2013) found that the total ozone exhibits an increase due to variability in QBO 50 hPa (QBO2) over the US, while a change in total ozone is found to be negative over Europe. However, results might be less significant; see Fig.…”
Section: Figmentioning
confidence: 99%
“…Secondly, the sensitivity of total ozone variability to the QBO signal has been discussed in Frossard et al (2013). They found that QBO 30 hPa (QBO1) has a negative contribution to total ozone variability over the US (Boulder) and some of Europe (Arosa), and the contribution is significant (smaller p value than 1 %).…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies investigated the evolution of low ozone episodes at mid-latitudes (Anton et al 2008;Bojkov and Balis 2001;Brönnimann and Hood 2003;Fitzka et al 2014;Frossard et al 2013;Hood et al 2001;Iwao and Hirooka 2006;James 1998;Koch et al 2005;Krzyscin 2002;Newman et al 1988;Petzoldt 1999;Rieder et al 2010aRieder et al , b, 2011Rieder et al , 2013. The definitions for low ozone episodes, often referred to as ozone miniholes, vary among studies, and to date, only few studies have analyzed changes in the UV field during low ozone episodes and the general connection between low ozone episodes and UV levels (e.g., Anton et al 2008;Bartlett and Webb 2000;Fragkos et al 2016;MartinezLozano et al 2011;McKenzie et al 1991;Rieder et al 2010c).…”
Section: Introductionmentioning
confidence: 99%